A Review on Regulation of Hybrid Solar Photovoltaic and Wind Drive Coordination - Pothuraju, P.; Venkatesan, M. (International Journal of Engineering and Technology, 2018)
Now a days electrical energy is essential to social development and for the economic growth of any country. Majorly the world facing the power generation problem.Â The fossil fuel sourcesare limited and needed to use properly. This huge power generation increases the green house effect.Â Hence to overcomeÂ this effect, prefer combined operation of Solar Photovoltaic (SPV)Â and Wind power generation systems. Due to high penetration ofÂ SPVÂ and wind systems in presen tenergy schememighteffectand form many practical issuesparticularly to individual systems and weak grids, with lack of control and ample loading capability. Hence,incorporating both SPV and wind energy systems to form an optimal arrangement, the effect offlexible nature of wind as well as solar energy can partlydeterminedbesides the whole arrangementsuits more efficient and reliable to operation.This paper presents the exploration on control schemesÂ of combined SPV and wind driveincorporationarrangements. Energy, incidence oscillations and harmonics are significant power quality disputes for grid mode as well as standalone arrangements having hugeeffect in weak networks. Thus can be determined to a hugelevel by having suitable arrangement, innovative reaction techniques with energy storage arrangement and good optimization of both grid onnected and standalone ,hybrid SPV and wind energy systems.